Digital Story Telling to Enhance Students’ Listening Skills - Mohammad Umar Fakhrudin; Yuni Alawaturrohmah Solihah; Turini; Suwandi; Willy Eka Septian (Journal of Literature Language and Academic Studies, 2023)
This study is to enhance the learning of listening comprehension for the seventh-grade students through digital storytelling. Action research was conducted to obtain the data. The findings indicated a notable improvement in students' listening comprehension learning, as evidenced by test results and assessment scores at each session. The mean score of students in the pre-test increased from 43.33 to 66.7 in the post-test, with a moderate N-gain score (N-gain = 0.31). Ultimately, digital storytelling proved effective in enhancing students' listening comprehension by serving as an engaging and enjoyable learning tool for students and a creative teaching resource for educators.